COSMIC-RAY EXPOSURE AGE AND HELIOCENTRIC DISTANCE OF THE PARENT BODIES OF ENSTATITE CHONDRITES ALH 85119 AND MAC 88136 - Nakashima D.; Nakamura T.; Okazaki R. (My University, 2006)
We measured concentrations and isotopic ratios of noble gases in enstatite (E) chondrites Allan Hills (ALH) 85119 and MacAlpine Hills (MAC) 88136. These two meteorites contain solar and cosmogenic noble gases. Based on the solar and cosmogenic noble gas compositions, we calculated heliocentric distances, parent body exposure ages, and space exposure ages of the two meteorites. The parent body exposure ages are longer than 6.7 Ma for ALH 85119 and longer than 8.7 Ma for MAC 88136. The space exposure ages are shorter than 2.2 Ma for ALH 85119 and shorter than 3.9 Ma for MAC 88136. The estimated heliocentric distances are more than 1.1 AU for ALH 85119 and 1.3 AU for MAC 88136. Derived heliocentric distances indicate the locations of parent bodies in the past when constituents of the meteorites were exposed to the Sun. From the mineralogy and chemistry of E chondrites, it is believed that E chondrites formed in regions within 1.4 AU from the Sun. The heliocentric distances of the two E chondrite parent bodies are not different from the formation regions of E chondrites. This may imply that heliocentric distances of E chondrites have been relatively constant from their formation stage to the stage of exposure to the solar wind. © The Meteoritical Society, 2006.